F.H. Bradley and secular and religious debates in the philosophy of history - Connelly, James (Philosophical Enquiries: Revue des philosophies anglophones, 2018)
This paper considers F. H. Bradley’s The Presuppositions of Critical History as a foundational document in philosophy of history, and its origin in debates in church history triggered by claims that biblical stories should be subject to the constraints of historical inquiry. Bradley asked by what criterion the historian should judge claims about the past, in particular, those contemporaneous with the events they report. He argues that history requires judgement which rests on absolute presuppositions, specifically the assumption of the uniformity of nature. Bradley asserts that, in historical testimony, we cannot accept any claim invoking causes or effects for which we have no present day analogy. The critical historian should thus discount whatever is contrary to natural law, and this implies ruling out the possibility of taking reports of the miraculous seriously. The paper concludes with an evaluation of Bradley’s claims in the light of Collingwood’s criticisms.